Ninth Five Year Plan 1997-2002 and Annual Plan-1997-98 Draft Proposals Volume II Part-X-B Social Services Government of Meghalaya - Planning Commission (Planning Commission, 1997)
The original outlay for Health Sector for the Eight Plan period is Rs.4000.00 lakhs, out of which Rs.2200,60 lakhs is for Minimum Needs Programme under Earmarked Sector. The agreed outlay by Annual Plans for the Eighth Plan is Rs.5702.54 lakhs and the anticipated expenditure is Rs 5527.29 lakhs. The proposed outlay for the Ninth Plan period is Rs 13170.00 lakhs out of which Rs.5836 is for MNP/BMS. The tentative outlay for 1997-98 is Rs.1730.00 lakhs, out of which Rs.1306.50 lakhs is for MNP/BMS.
Planning Department